Profile of fatty acids of Longissimus dorsi muscle and productive indicators of sheeps, supplemented with pods of Acacia cochliacantha, in grasslands native to dry tropics - Mireles, E. J.; Rodríguez, D.; Jordán, H.; Valdivia, M.; Ramírez, A.; García, A.; Olivares, J. (Cuban Journal of Agricultural Science, 2016)
Daily weight gain, hot carcass yield and profile of fatty acids of Longissimus dorsi muscle were determined in 30 Pelibuey-Black Belly x Dorper-Katahdin lambs, with 20 ± 2 kg of liveweight, supplemented with ground pods of Acacia cochliacantha, in irrigated native grasslands. The animals were selected at random and three treatments were designed: 1) grazing and 0 % of supplementation, 2) grazing plus 15 % of supplementation, and 3) grazing plus 30 % of supplementation with Acacia cochliacantha, according to the dry matter requirements. The grasslands were composed by shrubs, grasses and herbaceous plants. Daily weight gain, hot carcass yield, weight of liver, kidneys and heart, perirenal and pericardial fat, and profile of fatty acids were determined. The analysis of variance was applied to the data. There were no significant differences in daily weight gain (68, 59 and 63 g), hot carcass yield (37.08, 37.84 and 39.09 %), weight of viscera and intramuscular fat (1.59, 1.84 and 1.72 %). There was a C18:2-n6/c18:3-n3 (omega 6/omega 3) relation of 3.53, 3.25 and 3.38 in the Longissimus dorsi muscle, for the 0, 15 and 30 % supplementation groups, respectively. The treatment with 30 % of supplementation had the lowest content (P<0.05) of C22:1n-9, regarding the control treatment. It can be concluded that lambs in irrigated native grasslands, with or without supplementation of pods of Acacia cochliacantha, produced acceptable hot carcass yield and daily weight gains, and a close relation of C18:2-n6/c18:3-n3. There was only a decrease of erucic acid (C22:1n-9) in the Longissimus dorsi muscle of the supplemented animals. Key words: ovine, daily weight gain, intramuscular fat, supplementation, Acacia cochliacantha